Characterization of achondritic cosmic spherules from the Widerøefjellet micrometeorite collection (Sør Rondane Mountains, East Antarctica) - Soens, Bastien; Chernonozhkin, Stepan; González de Vega, Claudia; Vanhaecke, Frank; van Ginneken, Matthias; Claeys, Philippe; Goderis, Steven (Geochimica et Cosmochimica Acta, 2022)
Achondritic micrometeorites represent one of the rarest (ca. 0.5–2.1%) particle types among Antarctic micrometeorite collections. Here, we present major, trace element and oxygen isotope compositions on five vitreous, achondritic cosmic spherules (341–526 µm in size) recovered from the Widerøefjellet sedimentary trap in the Sør Rondane Mountains (SRMs) of East Antarctica. We also present the first iron isotope data for four of these achondritic cosmic spherules. The particles were initially identified based on the atomic concentrations of Fe-Mg-Mn and their distribution in Fe/Mg versus Fe/Mn space, spanning a relatively wide range in Fe/Mg ratios (ca. 0.48–1.72). The Fe/Mn ratios cover a more restricted range (22.4–31.7), comparable to or slightly below the values measured for howardite-eucrite-diogenite (HED) and martian meteorites. One particle (WF1801-AC3) displays an elevated Fe/Mn ratio of ∼78, comparable to the values determined for lunar rocks. The negative correlation observed between the CaO + Al2O3 contents and the Fe/Si ratios of achondritic spherules reflects both the mineralogy of the precursor materials, as well as the extent of volatilization experienced during atmospheric entry heating. This trend suggests that the primary mineralogy of precursor materials may have been compositionally similar to basaltic achondrites. Based on their distribution in Ca/Si versus Al/Si space, we argue that the majority of achondritic cosmic spherules predominantly sample pyroxene- and/or plagioclase-rich (i.e., basaltic) precursor bodies. Such precursor mineralogy is also inferred from their rare earth element (REE) patterns, which show resemblances to fine-grained basaltic eucrites or Type 1 achondritic spherules (n = 3 – av. REEN = 11.2–15.5, (La/Yb)N = 0.93–1.21), pigeonite-rich equilibrated eucrite precursors or Type 2 achondritic spherules (n = 1 – av. REEN = 27.9, (La/Yb)N = 0.10), and possibly Ca-phosphates from (primitive) achondritic bodies (n = 1 – av. REEN = 58.8, (La/Yb)N = 1.59). This is clearly ...